Analisis Pengembangan Bahan Ajar Bahasa Arab Berdasarkan Hasil Analisis Kebutuhan Peserta Didik - Ayuk Supiani; Fathul Maujud (Kartika: Jurnal Studi Keislaman, 2026)
The development of teaching materials that suit the needs of students is one of the important factors in increasing the effectiveness of Arabic language learning. However, there are still many teaching materials that are prepared without considering the needs, characteristics, and learning goals of students, so that they do not support the achievement of language competence optimally. This study aims to analyze the role of needs analysis in the development of Arabic teaching materials and identify the characteristics of teaching materials that are in accordance with the needs of students. This research uses a library research method with a qualitative descriptive approach. Data were obtained from various books, scientific articles, and research results relevant to the analysis of needs and development of Arabic teaching materials. The results of the study show that the main needs of students include vocabulary mastery, communication skills, contextual materials, integration of four language skills, and the use of technology in learning. In addition, teaching materials developed based on the results of needs analysis have been proven to be more relevant to the characteristics of students, able to increase learning motivation, and support the effectiveness of Arabic language learning. This study provides a theoretical contribution in the form of strengthening the importance of needs analysis as a foundation in the development of Arabic teaching materials that are student-centered and in accordance with the demands of modern learning